Disk Diffusion and Serial Dilution Tests of Susceptibility of Some Pathogenic Gram-Negative Bacilli and Enterococci to Carbenicillin and Ampicillin - Garner, Carol (1975)
Tests for susceptibility to ampicillin and carbenicillin were performed with 35 strains each of Klebsiella, Enterobacter, Serratia, and Proteus, 71 strains of Pseudomonas aeruginosa, and 68 strains of enterococci by serial dilution and disk-diffusion tests employing 10(−3) dilutions of overnight cultures as inocula for both. Commercial 10-μg ampicillin and 50- and 100-μg carbenicillin disks, and freshly prepared 10-, 50-, and 75-μg ampicillin and 10- and 50-μg carbenicillin disks were used. Results were displayed as cumulative distribution curves for both minimal inhibitory concentrations and zone diameters, and as scattergrams for correlating them. Differences in susceptibility to the two antibiotics were small for Klebsiella, Enterobacter, and Serratia and large for the others. The freshly prepared and commercial disks of the same content gave comparable zones. There was good correlation of zone diameter with each disk and the minimal inhibitory concentration. Among the ampicillin disks tested, none was useful for Pseudomonas; with the other species, the 10-μg disk, as well as those with higher ampicillin content, could discriminate susceptible from resistant strains. However, only the 75-μg disk selected some Klebsiella strains susceptible to high concentrations. The 50- and 100-μg carbenicillin disks were equally discriminating for most strains, but the higher concentration was more selective for Klebsiella. The 10-μg carbenicillin disk was as effective as the 50- and 100-μg disks for discriminating among Enterobacter, Serratia, Pseudomonas, and Proteus, but not for Klebsiella or enterococci. The 10(−3) inoculum gave zone sizes considerably larger than those reported by other workers who used the standard Kirby-Bauer method.